Portrait of a naval officer - Shmith, Athol, 1914-1990 (1949)
Portrait of a naval officer holding his hat, his sleeve stripes indicate that he is a captain.
Title from caption on reverse.
Part of the collection: Collection of fashion photographs.
Inscriptions: "A.S. 202."--On reverse.
Also available online
Donated by Athol Shmith in 1979.
Keywords: Australia. -- Royal Australian Navy. -- Officers -- Portraits; Navies -- Officers -- Portraits